ANALISIS PENGARUH SUHU PENGERINGAN TERHADAP MUTU ORGANOLEPTIK PUNDANG SELUANG - Helmi Harris; Aan Agustiawan (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2018)
his study aims to determine the effect of drying temperature using electric ovens and sunlight on organoleptic quality of Pundang Seluang. This study used a Randomized Block Design (RBD) with 4 (four) levels of treatment, each treatment performed 3 (three) replications. The treatment in this study is the use of 4 (four) temperature variations, namely: T0 (Sun drying as a Control, T1 (Drying using an electric oven temperature of 40 0C), T2 (Drying using an electric oven at 45 0C), T3 (Drying using an oven electric temperature 50 0C) The parameters observed included organoleptic quality analysis The results showed that drying using sunlight with an average temperature of 42 0C requires a drying time of 14 hours, with yield 22.00 %, organoleptic value 7.88 Electric oven drying, the best treatment is drying with a temperature of 45 0C (T2) Quality characteristics of the treatment T2 Drying using an electric oven temperature of 45 0C with organoleptic value 7.90, yield 22.33 %, drying time 14.09 hours. Drying uses sunlight to produce a lawn with a brighter and less brittle appearance Keywords: Organoleptic Quality, Drying, Pundang Seluang, and Temperature Variation